Percepção de auditores independentes e auditados sobre aaplicação da lei Sarbanes-Oxley nos controles internos - Duílio Ulhôa Leite (2014)
One of the greatest revolutions in the organizational structure of internal controls in recent years occurred with the promulgation of the Sarbanes-Oxley Act (SOX), which required more robust control procedures in order to regain the reliance of investors and market after the accounting scandals that occurred between 2000 and 2002 in the United States. In this context, the purpose of this research was to identify the perception of independent auditors and audited by these auditors about the implementation of Sarbanes-Oxley (SOX) Act in the internal controls of organizations. For this purpose, a questionnaire was designed with 6 questions related to the profile of the respondents and 29 questions related to the Act, subdivided into six topics: i) generation of more reliable information, ii) risks related to the processes, iii) maturity of internal controls; iv) importance attributed to SOX and new internal controls from the Act, v) costs and benefits, and vi) influence on the professions of independent auditor, internal auditor and accountant. The sample consisted of independent auditors that assess the internal control structure of Brazilian companies required to comply the Act and by employees who perform internal controls in these entities (audited). 93 answers by independent auditors and 50 answers by audited were received, totaling 143 responses. Based on these responses, was identified the perception of respondents to each question, that were submitted to difference of means tests, in order to verify if there were differences in perception between these two groups (independent auditors and audited). It was found that in all the topics of the questionnaire, in general, both of independent auditors and audited, attributed a positive perception towards the implementation of SOX in internal controls of organizations, exceptions occurring in one of the eight questions of the topic "generation of more reliable information, two of the six questions of the topic "importance attributed to SOX and new internal controls from the Act" and in one of the four questions of the topic "costs and benefits". Additionally, it was observed that in eight questions, distributed among the six topics of the questionnaire, although the majority of respondents from both groups have attributed a positive perception to the Act, the independent auditors attributed a more positive perception compared to the audited. Moreover, in another question, the groups had contrary perceptions, with the majority of the independent auditors disagreeing with the statement that SOX causes unnecessary controls in organizations, whereas most audited agreed with this statement. Finally, by a multiple linear regression, it was found that, as expected, the variables "specialization area", "area of operation" and "post" statistically influence the perception of respondents about the implementation of SOX in internal controls of organizations. On the other hand, the variables "gender", "age" and "training related to SOX" were not statistically significant.